Aditivos naturales y sintéticos empleados por la industria avícola en américa para dar coloración de la yema de huevo - Valdivieso Luna, David Alexis (2020)
Poultry farmers see a need for innovation in pigment options for egg yolks, arising the problem of this document: the lack of a database regarding the use of colorants used inlaying birds. The objective of this research is to collect information regarding the coloring of the egg yolk in laying birds with different natural and synthetic pigments used by the poultry industry in America. To assess the compatibility of the articles with the topic, the PRISMA method was used with certain inclusion criteria such as: the selection of articles aimed at the pigmentation of egg yolks for human consumption, performed of laying birds, using natural pigmentants as synthetics and exclusive to America. Thus excluding any item that it has not been carried out in laying birds and outside the American continent. Among the results obtained, two are important to mention: first, of the 12 selected articles 11 of them are based on natural pigmentants of which the most preferred pigment in the poultry industry is spirulina, followed by cornmeal gluten. Second, there is only 1 published article referring to synthetic pigmentants, the: 3 Nitro, which is has been restricted since February 2014 by the FDA. Finally, information was collected about the methods of assessing the color for the egg yolk, these being the following: colorimetric range, reflectance and digital colorimeters.